2022
DOI: 10.1091/mbc.e21-05-0232
|View full text |Cite
|
Sign up to set email alerts
|

Deafness mutation in the MYO3A motor domain impairs actin protrusion elongation mechanism

Abstract: Class III myosins are actin-based motors proposed to transport cargo to the distal tips of stereocilia in the inner ear hairs cells and/or to participate in stereocilia length regulation, which is especially important during development. Mutations in the MYO3A gene are associated with delayed onset deafness. A previous study demonstrated that L697W, a dominant deafness mutation, disrupts MYO3A ATPase and motor properties but does not impair its ability to localize to the tips of actin protrusions. In the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 61 publications
3
8
0
Order By: Relevance
“…A MYO3B/3A fusion protein that replaces the MYO3A motor and neck with the MYO3B motor and neck (MYO3B.3Atail) was able to localize to the tips of filopodia in COS7 cells, though the amount of localized myosin, filopodia length, and filopodia density were all reduced ( 6 ). Similarly, we found that the loss-of-function deafness-associated mutation L697W reduced the motor function of MYO3A in vitro , as well as in COS7 cells ( 5 , 13 ). Kinetic studies demonstrated a reduction in actin-activated ATPase and in vitro motility velocity, while COS7 cells transfected with MYO3A L697W produced filopodia of shorter lengths that extended at a slower rate than WT.…”
supporting
confidence: 56%
See 3 more Smart Citations
“…A MYO3B/3A fusion protein that replaces the MYO3A motor and neck with the MYO3B motor and neck (MYO3B.3Atail) was able to localize to the tips of filopodia in COS7 cells, though the amount of localized myosin, filopodia length, and filopodia density were all reduced ( 6 ). Similarly, we found that the loss-of-function deafness-associated mutation L697W reduced the motor function of MYO3A in vitro , as well as in COS7 cells ( 5 , 13 ). Kinetic studies demonstrated a reduction in actin-activated ATPase and in vitro motility velocity, while COS7 cells transfected with MYO3A L697W produced filopodia of shorter lengths that extended at a slower rate than WT.…”
supporting
confidence: 56%
“…We examined the biochemical and biophysical properties of the MYO3A motor by expressing and purifying a construct containing the motor domain and neck region but lacking the kinase domain, and containing a C-terminal GFP tag (MYO3A 2IQ; see structure and diagram in Fig. 1 , A and B ) ( 5 , 6 ). To investigate the cellular function of MYO3A we expressed a full-length construct lacking the kinase domain and containing an N-terminal GFP tag (MYO3A; see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Malat1 encodes a long non-coding RNA that is highly abundant in the nervous system and plays a role in neuronal cell injury; 39 this gene was increased by mTBI and decreased by T4 at 7-day but the direction was opposite at 24hr and 21-day post-injury. Myo3a is a cytoskeleton gene and variants are related to hearing and vision loss, 40,41 and this gene was primarily increased by mTBI but inhibited by T4 at 21-day post-injury. Ppia mediates inflammation and has shown both beneficial effects intracellularly 42 and detrimental function extracellularly.…”
Section: Resultsmentioning
confidence: 99%